2015
DOI: 10.1111/jbi.12543
|View full text |Cite
|
Sign up to set email alerts
|

Geographical origins, migration patterns and refugia of Sibbaldia procumbens, an arctic–alpine plant with a fragmented range

Abstract: Aim Many plants, especially at high latitudes, have both widespread and highly discontinuous geographical distributions. To increase understanding of how such patterns originate, we examine genetic patterns in the arctic-alpine plant Sibbaldia procumbens. We evaluate the contributions of refugia and the role of long-distance dispersal in shaping the current range of this species.Location Northern Hemisphere, especially North America.Methods We sampled Sibbaldia from 176 localities, including 168 for S. procumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 60 publications
(91 reference statements)
3
32
1
Order By: Relevance
“…Similar patterns of divergent southern populations are found in many other arctic-alpine plant species, e.g. Ranunculus glacialis (Schönswetter, Paun, Tribsch, & Niklfeld, 2003), Arabis alpina (Koch et al, 2006), Oxyria digyna (Allen, Marr, McCormick, & Hebda, 2012), Saxifraga oppositifolia (Winkler et al, 2012) and Sibbaldia procumbens (Allen, Marr, McCormick, & Hebda, 2015).…”
Section: Other Refugia and Postglacial Contact Zonessupporting
confidence: 67%
See 1 more Smart Citation
“…Similar patterns of divergent southern populations are found in many other arctic-alpine plant species, e.g. Ranunculus glacialis (Schönswetter, Paun, Tribsch, & Niklfeld, 2003), Arabis alpina (Koch et al, 2006), Oxyria digyna (Allen, Marr, McCormick, & Hebda, 2012), Saxifraga oppositifolia (Winkler et al, 2012) and Sibbaldia procumbens (Allen, Marr, McCormick, & Hebda, 2015).…”
Section: Other Refugia and Postglacial Contact Zonessupporting
confidence: 67%
“…Dunlop () hypothesized a cryptic LGM refugium in British Columbia or south of the ice in the Cordilleran Ecoregion, and several other studies of tundra plant species have found unique haplotypes in British Columbia (e.g. Allen et al, ; Allen et al, ; Guest & Allen, ; Marr, Allen, Hebda, & McCormick, ).…”
Section: Discussionmentioning
confidence: 99%
“…(2004) and plant material and AFLP data for S. procumbens has previously also been published in Allen et al . (2015) and Alsos et al .…”
Section: Methodsmentioning
confidence: 98%
“…The major patterns we see in the complex—persistence to the south of the ice sheets with climate refugia in the Rockies and at least two regions of the Cascade‐Sierra axis—are shared by other taxa in the region (e.g., Allen, Marr, McCormick, & Hebda, ; Gugger & Sugita, ; Gugger et al., ). However, we find no support for survival in Beringia, in nunataks, or the ice‐free corridor, whereas ample evidence exists for other taxa (e.g., Abbott & Comes, ; Alsos, Engelskjøn, Gielly, Taberlet, & Brochmann, ; Beatty & Provan, ; Godbout et al., ; Marr, Allen, Hebda, & McCormick, ).…”
Section: Discussionmentioning
confidence: 92%